Modulating Yogurt Fermentation Through Pulsed Electric Fields and Influence of Milk Fat Content - Graciela A. Miranda-Mejía; Anaberta Cardador-Martínez; Viridiana Tejada-Ortigoza; Mariana Morales-de la Peña; Olga Martín-Belloso (Foods)
Yogurt is a highly consumed dairy product valued for its nutritional and probiotic properties. Its production involves the use of lactic acid bacteria, which drive biochemical transformations during fermentation. Optimizing fermentation time without compromising yogurt quality is essential for improving processing efficiency. Pulsed electric fields (PEFs) constitute a promising technology that stimulates microbial activity. In this study, a yogurt starter inoculum suspended in milk (IM) with different fat content (0.5–2.8%) was treated with low-intensity PEFs (1 kV/cm, 800–1600 µs) to enhance fermentation kinetics. pH, soluble solids, lactose, lactic acid, and riboflavin concentrations were monitored during 6 h, comparing PEF-treated IM (PEF-IM) and untreated IM (C-IM). PEF-treatments applied to IM reduced the fermentation time of inoculated milk by 4.3–20.4 min compared to C-IM. The lowest fermentation time (5.1 ± 0.16 h) was observed in milk added with PEF-IM (2.8% fat) treated at 1 kV/cm for 1600 µs. Milk inoculated with PEF-IM exhibited enhanced lactose consumption (1.6–3.1%) and higher lactic acid production (7.2%) than milk with C-IM. Riboflavin concentration (0.9–7%) decreased between 2 and 4 h, but it stabilized at the end of fermentation. Obtained results suggest that PEFs promote reversible electroporation in microbial cells, facilitating nutrient uptake and acidification, making it a promising assisted-fermentation approach to improve yogurt production.